A Facile Strategy to Improve the Electrochemical Performance of Porous Organic Polymer‐Based Lithium–Sulfur Batteries. Issue 12 (29th July 2019) - Yang, Shuhao; Liu, Qianhui; Lu, Qiongqiong; Zhang, En; Arrozi, Ubed SF.; Li, Hejun; Kaskel, Stefan; Xu, Fei; Wang, Hongqiang
Abstract : Porous organic polymers (POPs), with features of permanent nanopores and designable frameworks, show great promise as sulfur host materials to restrain the shuttling of polysulfides, one of the main obstacles in the development of lithium–sulfur batteries. However, the simple physical entrapment from weak intermolecular interactions via a typical melt‐diffusion method results in the diffusive loss of polysulfides that has thus far restricted their potential. Herein, a facile strategy for introducing chemical covalent interactions between POPs and sulfur via the regulation of sulfur infiltration temperature is reported. The results show that increasing the temperature to a suitable value, e.g., 400 °C, for a fluorinated triazine‐based framework (FCTF), enables chemical bonding between the sulfur and aromatic FCTF backbone. Benefitting from the synergetic chemical and physical confinement effect, the shuttling of polysulfides can be efficiently restrained. As a result, the sample features superior sulfur utilization, high‐rate performances, and good cycle stability, as compared with the sample with only physical confinement. The proposed strategy can also be extended to other POPs, such as the boroxine‐linked covalent organic framework, by judiciously tailoring the infiltration temperatures. The findings disclose the important role of infiltration temperatures in developing efficient cathode host materials for lithium–sulfur batteries. Abstract : A porous organic architecture is developed as a dual‐confinement host cathode in lithium–sulfur batteries via a simple temperature‐regulating strategy. Increasing the sulfur infiltration temperature to a suitable value triggers covalent attachment of sulfur on pore walls. The synergetic chemical and physical confinement effect restrains the shuttling of polysulfides, thus leading to superior sulfur utilization, high‐rate performances, and good cycle stability.